2021
DOI: 10.1111/imj.15590
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines for the diagnosis and management of cryptococcosis and rare yeast infections in the haematology/oncology setting, 2021

Abstract: Cryptococcosis caused by the Cryptococcus neoformans-Cryptococcus gattii complex is an important opportunistic infection in people with immunodeficiency, including in the haematology/oncology setting. This may manifest clinically as cryptococcal meningitis or pulmonary cryptococcosis, or be detected incidentally by cryptococcal antigenemia, a positive sputum culture or radiological imaging. Non-Candida, non-Cryptococcus spp. rare yeast fungaemia are increasingly common in this population. These consensus guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 213 publications
0
33
0
2
Order By: Relevance
“…The identification of C. neoformans and C. gattii to the species level is important to guide treatment regimens and inform clinical progression and outcomes [ 1 , 3 , 4 ]. Although the differentiation of the two species from culture-positive clinical specimens can be performed reliably by matrix-assisted laser desorption ionization-time of flight mass spectrometry, inoculation onto canavanine-glycine-bromothymol (CGB) agar [ 24 , 25 ], or a variety of molecular methods, including multi-locus sequence typing, PCR fingerprinting and amplified fragment length polymorphism analysis [ 7 , 8 ], these approaches are either slow (up to several days) and/or require access to laboratories performing genotyping methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification of C. neoformans and C. gattii to the species level is important to guide treatment regimens and inform clinical progression and outcomes [ 1 , 3 , 4 ]. Although the differentiation of the two species from culture-positive clinical specimens can be performed reliably by matrix-assisted laser desorption ionization-time of flight mass spectrometry, inoculation onto canavanine-glycine-bromothymol (CGB) agar [ 24 , 25 ], or a variety of molecular methods, including multi-locus sequence typing, PCR fingerprinting and amplified fragment length polymorphism analysis [ 7 , 8 ], these approaches are either slow (up to several days) and/or require access to laboratories performing genotyping methods.…”
Section: Discussionmentioning
confidence: 99%
“…A global study of the molecular epidemiology of Cryptococcus found that in Australia the prevalent genotypes are VNI (131/164) and VNII (25/164) for C. neoformans and VGI (179/300) and VGII (121/300) for C. gattii [ 26 ]. Whilst the relevance of detecting known genotypes remains uncertain in clinical practice [ 4 ], global travel and immigration from regions where other genotypes are more frequent make it important to have an all-encompassing approach for a diagnostic assay. Of note, we designed the assay to directly detect and distinguish between C. neoformans and C. gattii in clinical specimens, because this addresses the major clinical need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, cryptococcosis management guidelines did not consider it necessary to establish the species of Cryptococcus in clinical practice [ 48 , 52 , 53 ]. The most recent guidelines recommend doing this speciation in the clinical laboratory due to the differences in the morphology, biology, and phylogenetics of the two species [ 54 , 55 ]. Mortality and sequelae of CNS cryptococcosis due to C. gattii remain high (20.2%) [ 56 ].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%